Effectiveness of Rosmarinus officinalis and Centella asiatica Nanoemulsions Against Caspase 3 Gestational Diabetes Mellitus Expression - Sutini Lamadi; Fajar Dwi Prastiwi; Tri Yudani Mardining Raras; Husnul Khotimah; I Wayan Arsana Wiyasa (Medical Laboratory Technology Journal, 2023)
Gestational diabetes mellitus (GDM) is closely related to oxidative stress conditions in insulin resistance conditions that increase Reactive Oxygen Species (ROS) against the body's defense antioxidant mechanism. Chronic complications due to hyperglycemia in patients with GDM increase BAX / BCL2 levels which then activates the change of procaspase 3 to caspase 3, an activator of apoptosis. This study aims to determine the effect of the combination of Rosmarinus officinalis and Centella asiatica nanoemulsions on caspase 3 expressions in zebrafish models of gestational diabetes mellitus, with a posttest-only controlled group design. The samples were divided into five groups, namely K- (EM), K+(EM+3% Glucose), P1, P2 and P3 (3% Glucose + Combination of Rosmarinus officinalis and Centella asiatica 2.5μg/ml, 5μg/ml and 10μg/ml), which will be tested for PEPCK and Caspase expression at the age of 3dpf using Real Time-PCR. The results of the correlation test of the group with caspase 3 obtained (p = 0.045) negative direction. These results show that the combination of Rosmarinus officinalis and Centella asiatica nanoemulsion decreased Caspase 3 expression in zebrafish models of gestational diabetes mellitus. The combination of Rosmarinus officinalis and Centella asiatica nanoemulsion has the potential to reduce blood glucose levels and reduce the risk of apoptosis in gestational diabetes mellitus patients.